Plant Oil‐Derived Epoxy Polymers toward Sustainable Biobased Thermosets. Issue 11 (21st March 2017) - Wang, Zhongkai; Yuan, Liang; Ganewatta, Mitra S.; Lamm, Meghan E.; Rahman, Md Anisur; Wang, Jifu; Liu, Shengquan; Tang, Chuanbing
Abstract : Epoxy polymers derived from soybean oil are utilized to prepare sustainable biobased thermosets with mechanical properties superior to those counterparts with the use of epoxidized soybean oil or other compounds with a much lower number of epoxides per molecule. Abstract : Epoxy polymers (EPs) derived from soybean oil with varied chemical structures are synthesized. These polymers are then cured with anhydrides to yield soybean‐oil‐derived epoxy thermosets. The curing kinetic, thermal, and mechanical properties are well characterized. Due to the high epoxide functionality per epoxy polymer chain, these thermosets exhibit tensile strength over an order of magnitude higher than a control formulation with epoxidized soybean oil. More importantly, thermosetting materials ranging from soft elastomers to tough thermosets can be obtained simply by using different EPs and/or by controlling feed ratios of EPs to anhydrides.